THE PARAMETERS OF VIDEO INFORMATION COMPRESSION PROCESS IN DISTRIBUTED SYSTEMS - Skrupskiy, S. U.; Lutsenko, N. V.; Skrupskaya, L. S. (Radio Electronics, Computer Science, Control, 2012)
The paper deals with the analysis of the main parameters of video information compression process in distributed systems. The influence of these parameters on compression coefficient, distortion level and compression time of video information in distributed system is experimentally investigated.